Sophocles a very short introduction - Hall, Edith 1959- (Very short introductions, 2025)
This volume introduces the life, work, and influence of one of the greatest dramatists of all time, Sophocles the Athenian, placing his plays within their historical context, and explaining the conventions of ancient Greek tragic theatre